A non-synonymous single nucleotide polymorphism in SIRT6 predicts neurological severity in Friedreich ataxia - Rodden, Layne N.; Rummey, Christian; Dong, Yi Na; Lagedrost, Sarah; Regner, Sean; Brocht, Alicia; Bushara, Khalaf; Delatycki, Martin B.; Gomez, Christopher M.; Mathews, Katherine; Murray, Sarah; Perlman, Susan; et al. (Frontiers in Molecular Biosciences, 2022)
Introduction Friedreich ataxia (FRDA) is a recessive neurodegenerative disease characterized by progressive ataxia, dyscoordination, and loss of vision. The variable length of the pathogenic GAA triplet repeat expansion in the FXN gene in part explains the inter-individual variability in severity of disease. The GAA repeat expansion leads to epigenetic silencing of FXN; therefore, variability in properties of epigenetic effector proteins could also regulate the severity of FRDA. Methods In an exploratory analysis, DNA from 88 individuals with FRDA was analyzed to determine if any of five non-synonymous SNPs in HDACs/SIRTs predicted FRDA disease severity. Results suggested the need for a full analysis at the rs352493 locus in SIRT6 (p.Asn46Ser). In a cohort of 569 subjects with FRDA, disease features were compared between subjects homozygous for the common thymine SIRT6 variant (TT) and those with the less common cytosine variant on one allele and thymine on the other (CT). Biochemical properties of both variants of SIRT6 were analyzed and compared. Results Linear regression in the exploratory cohort suggested that a SNP (rs352493) in SIRT6 correlated with neurological severity in FRDA. The follow up analysis in a larger cohort agreed with the initial result that the genotype of SIRT6 at the locus rs352493 predicted severity of disease features of FRDA. Those in the CT SIRT6 group performed better on measures of neurological and visual function over time when compared to those in the more common TT SIRT6 group. The Asn to Ser amino acid change resulting from the SNP in SIRT6 did not alter expression or enzymatic activity of SIRT6 or frataxin but, iPSC-derived neurons from people with FRDA in the CT SIRT6 group showed whole transcriptome differences compared to those in the TT SIRT6 group. Conclusions People with FRDA in the CT SIRT6 group have less severe neurological and visual dysfunction compared to those in the TT SIRT6 group. Biochemical analyses indicate that the benefit conferred by T to C SNP in SIRT6 does not come from altered expression or enzymatic activity of SIRT6 or frataxin but is associated with changes in the transcriptome.